The influence of biofuel energy production on the exports of the palm oil industry in Malaysia: A panel GMM and robust standard error approach - Chow, Kok Fong (Energy Economics Letters, 2023)
In recent years, there has been a consistent and significant increase in the consumption of biofuels by countries across the globe. Numerous governments have implemented distinct quotas and objectives aimed at promoting and governing the augmented utilization of biofuels. The demand for biofuel is growing in European countries, which increases the export of biofuel energy in parent countries such as Malaysia. The Malaysian government has suggested receiving different sustainability certifications that are relevant to the biofuel industry. The Malaysian government has made it compulsory to attain environmental sustainability for oil-producing certification. The purpose of this article is to examine the role of biofuel energy production on the exports of the palm oil industry in Malaysia. This study uses the annual data of Malaysian palm oil exporters from 2009 to 2018 and employs the generalized method of moments (GMM) and the robust standard error methodologies. The findings showed that the production of palm oil plays a positive role in the exports of Malaysia’s palm oil industry. This study will serve as a guide for future research in this area and for the authorities when formulating policies regarding exports. It is recommended that these authorities should put extra emphasis on the productivity of the palm oil industry to further enhance Malaysia’s exports of biofuel, and the government needs to implement regulations to protect the environment.